Gaya Hidup Konsumerisme dan Komodifikasi Hijab di Era Instagram pada Akun Selebgram @Megaiskanti - Aiza Nabilla (Connected: Jurnal Ilmu Komunikasi, 2021)
A Commodity is a use-value that is used as an exchange-value. The use-value of this paper will be to use the hijab, which was originally a symbol of Islam, which has now become a business sphere, especially in Instagram, by making a Muslim commodity that sells faces or images of using one of the celebrities with 867,000 followers, namely Mega Iskanti @megaiskanti. This study uses a phenomenological approach with data interview techniques to five hijab users and Instagram followers of @megaiskanti. Personal branding is one of the most influential on Instagram followers. Hence, digital marketing communication becomes effective. Because this research focuses on the culture of consumerism and the commodification of the hijab, the five informants gave their information that they would be wasteful depending on the hijab used by who the selebgram was. Seeing from the face, image quality, price, and brand are taken into consideration. The use of Instagram has also become a new lifestyle to carry out a culture of consumerism.